Sexual Dimorphism in Modern Javanese Crania: A Metric Approach - Ashfyatus Saidah; Myrtati Dyah Artaria (Jurnal Biosains Pascasarjana, 2022)
Establishing the biological profile of an unknown skeleton is one of forensic anthropologist main tasks; sex is one of them. In sexing the skulls, specific standard assessment designed for each population can improve the accuracy rate due to its population-specific traits. This study aims to describe the sexual dimorphism in contemporary Javanese crania while employing metric methods. The measurements of 50 male and 37 female crania were traditionally collected from nine craniometric points (i.e., g-op, eu-eu, ft-ft, zy-zy, n-pr, n-ns, apt-apt, go-go, n-gn) using calipers. This study found that out of nine measuring points, two (ft-ft, apt-apt) variables does not differ significantly between the male and female samples. This indicates that, in accordance with previous studies, ft-ft and apt-apt are not good predictors for sex. Future studies observing the non-metric sexual dimorphism on Javanese crania would serve as a meaningful aid in improving the accuracy and reliability when sexing Javanese crania.